Ukraińska mniejszość narodowa w Telewizji Polskiej. Analiza programów dla ukraińskiej mniejszości przed, podczas i po Euro¬majdanie na Ukrainie - Banytska, Tetyana (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This article is an attempt to assess the quality of television programs targeted to Ukrainiannational minority in Poland. Public media in Poland have an obligation  of broadcasting programs for the minorities in their languages, which is imposed by the law on broadcasting. For the Ukrainian minority the Polish public television broadcasts three programs: „Przegląd ukraiński”, „Ukraińskie wieści” oraz „Telenowyny”. In this article the most important quality issues of these programs, such as duration of programs, subject diversity, methods of translation, technical aspects as well as the way of showing the civil unrest in Ukraine known as Euromaidan, are presented. An analysis was conducted within the timespan before, during and after the wave of demonstrations  in Ukraine (from 21 July 2013 to 22 June 2014).